2018
DOI: 10.1590/1981-22562018021.170158
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the feet of institutionalized elderly persons

Abstract: Objective: The present study aimed to identify the most frequent changes to the feet of institutionalized elderly persons. Method: A descriptive study was conducted with elderly persons living in long-term care facilities in the city of Passo Fundo, Rio Grande do Sul, Brazil. A total of 174 people aged 60 years and over of both genders were surveyed regardless of health conditions. Those with amputations, burns or who were undergoing surgery of the lower limbs were excluded. Data were collected through the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%